Application of Digital Media and Deep Learning to Hydrocarbon Materials at the High School Level: Systematic Literature Review - Syifaul Auliya; Sri Handayani (Universitas Negeri Yogyakarta, 2025)
This study aims to analyze the use of digital media and deep learning learning on hydrocarbon materials and their derivative compounds at the high school level through the Systematic Literature Review (SLR) approach. The study was conducted by analyzing various journals from Scopus and Google Scholar data using the keywords